[PP.23.16] TIME INTEGRATED SYMPATHETIC ACTIVITY CHANGES PARALLEL SIMULTANEOUS BP CHANGES AFTER RENAL DENERVATION. (September 2016) - Seravalle, G.; Brambilla, G.; Dell'Oro, R.; Trevano, F. Quarti; D'Arrigo, G.; Mallamaci, F.; Tripepi, G.; Zoccali, C.; Grassi, G.
Abstract : Objective: Renal denervation (RDN) reduces BP levels in treatment-resistant essential hypertension but there is apparently no relationship between sympathetic activity and BP changes after this intervention. We reassessed the problem in an incident series of 29 patients with ABPM documented resistant hypertension by measuring repeatedly (from 2 to 5 times) MNSAC and simultaneous (in lab) standardized BP and analyzed data by a novel statistical approach. Design and method: In all patients ABPM was performed the day before the MNSAC recording session. Since MNSAC is highly repeatable and stable over-time, the novel analytical approach calculates the proportional (%) difference between the expected area under the curve of repeated MSNAC measurements assuming that renal denervation has no effect on this variable (i.e., a rectangular area formed by individual baseline value [short side] and the individual time of observation [long side]) and the actual area under the MSNAC curve. The same calculation is applied to simultaneous BP and heart rate data Results: Overall RDN reduced BP over-time (SBP: from 175 ± 14 to 160 ± 19 mmHg; DBP: from 96 ± 11 to 88 ± 9 mmHg). MNSAC showed a parallel trend (from 67 ± 13 to 53 ± 17 burst/100 HR). HR did not change over-time (from 65 ± 12 to 64 ± 11 beats/min, In Mixed Linear Modelling (MLM) analyses, there was no relationship between SBP (r = 0.03, p = 0.72) and DBP (r = 0.03, p = 0.67) values over time and concomitant values of MSNA after RDN. The re-analyzing by MLM showed a strong relationship between proportional changes in MNSAC over time and simultaneous proportional changes in BP but not with HR (r = 0.28, p = 0.13). Likely due to the non-simultaneous nature of measurements and the influence of daily living environment, no relationship was found between MNSAC and ABPM. Conclusions: The proportional time-integrated BP-lowering effects of RDN are strongly associated with simultaneous time-integrated changes in MNSAC while no such time trend emerges in analyses of in-lab or ABPM data by the conventional MLM. These findings indicate that integrated sympathetic activity changes in the short and medium term rather than single measurements capture the pathophysiological relevance of the sympathetic system in the BP response to renal denervation.